Canine leptospirosis in stray and sheltered dogs: a systematic review. (21st June 2022) - Costa, Anna Cecília Trolesi Reis Borges; Colocho, Raisa Abreu Bragança; Pereira, Carine Rodrigues; Lage, Andrey Pereira; Heinemann, Marcos Bryan; Dorneles, Elaine Maria Seles
Abstract: The aim of this systematic review was to investigate the prevalence of leptospirosis among stray and sheltered dogs worldwide. Six databases were searched, which resulted in the retrieval of 476 articles. Sixty articles were selected for analysis according to 10 quality criteria. Among the selected papers, 26 papers [43.4% (26/60)] met five of the 10 quality criteria established, 10 papers [16.7% (10/60)] met three criteria, nine papers [15.0% (9/60)] met four criteria, six papers [10.0% (6/60)] met six criteria, four papers [6.7% (4/60)] met eight criteria, and three papers [5.0% (3/60)] met nine of the 10 criteria, whereas two papers [1.7% (1/60)] met two and seven [1.7% (1/60)] criteria. Publications originated mainly from the Americas [45.0% (27/60)] and in the last 16 years (2003–2019) [81.7% (49/60)], and most of the sampled dogs were stray dogs [65.0% (39/60)]. The most commonly used diagnostic test for leptospirosis was the microscopic agglutination test [78.4% (47/60)] followed by polymerase chain reaction [21.7% (13/60)], and the most common serovars were Canicola [71.4% (35/49)], Icterohaemorrhagiae [65.3% (32/49)], Grippotyphosa [40.8% (20/49)], and Pomona [40.8% (20/49)]. In conclusion, our results showed that Leptospira spp. are present in unowned dogs worldwide; however, the low-methodological quality of the recovered cross-sectional studies precluded a meta-analysis.